Refleksi Penerapan Akuntansi Berbasis Akrual: Simbolis atau Substantif? - Aditya Agung Satrio (Jurnal Eksplorasi Akuntansi, 2024)
This study aims to investigate the relationship between the application of accrual-based accounting and performance, using the institutional theory perspective. The study divides performance into two aspects: operational and financial performance. The data used in this study consists of 3,252 observations from local governments in Indonesia from 2011 to 2017. This research provides empirical evidence on the relationship between the implementation of accrual-based accounting and government performance, which is still limited. The results indicate a positive correlation between accrual-based accounting implementation and performance, as measured by both operational and financial parameters. The Indonesian government has adopted accrual-based accounting from the International Public Sector Accounting Standards (IPSAS) in a substantial manner, rather than just symbolically, in order to gain international legitimacy. The study's results are expected to inform the government on how to enhance the quality of financial statements and understanding of the implementation of accrual-based accounting in Indonesia. The study found that the perception of accrual-based accounting implementation varies across regions.